How successful is the Higher Institute of Communications and Navigation, Kuwait, in reducing dependence on expatriates - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
The need for skilled and semi-skilled indigenous manpower in the gulf states (e.g., Kuwait. Qatar, United Arab Emirates) is highly noted in the related literature. Technical and vocational education is considered as a dual type of education system that allow students to transfer what they have learned in classrooms, workshops, and laboratories into real work environment. It is the ultimate solution, particularly for the gulf states, to overcome and/or reduce the rate of dependance on expatriates especially in essential sectors in their economy (e.g., oil, electricity and water, health sector). The governments of the gulf states have realized the urgent need to forge technical and vocational colleges and institutions hoping to close the gap with industries and business. Technical and vocational education is completely different from formal education and thus requires a careful design, planning, and monitoring to ensure meeting industrial and business current and future requirements. However, the success of technical and vocational education would depend, to great extent, on the type of management since it requires a specific knowledge, skills, and attitudes that are distinguished technical and vocational education from any other types of education. The Higher Institute of Communications and Navigation, HIC&N, was forged by the Kuwaiti Government with the aim to equipped local manpower with the know-how and know-why that are mostly needed by local industries. The research is focus on measuring the perception of a sample of heads of departments at the Ministry of Communications towards the quality of HIC&N graduates. The research is based on extensive field work that encompasses a review of the related literature, interviews with a sample of heads of departments at the Ministry Communications to assess the quality of field training program and the standard of the HIC&N graduates. Finally, the research will argue that unless the HIC&N recognize and appreciate the value of building a strong linkage with local industries, its contribution in tackling the shortage of skilled and semi-skilled indigenous in essential sectors on the economy will be below the government expectations, thus continuing relaying on expatriates for years ahead.